2009
DOI: 10.1128/aem.02942-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of P450 Monooxygenases in the Degradation of the Endocrine-Disrupting Chemical Nonylphenol by the White Rot Fungus Phanerochaete chrysosporium

Abstract: The white rot fungus Phanerochaete chrysosporium extensively degraded the endocrine disruptor chemical nonylphenol (NP; 100% of 100 ppm) in both nutrient-limited cultures and nutrient-sufficient cultures. The P450 enzyme inhibitor piperonyl butoxide caused significant inhibition (ϳ75%) of the degradation activity in nutrient-rich malt extract (ME) cultures but no inhibition in defined low-nitrogen (LN) cultures, indicating an essential role of P450 monooxygenase(s) in NP degradation under nutrient-rich conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Members from CYP5144 and CYP63 exhibit catalytic activities toward environmentally persistent and toxic high-molecular-weight polycyclic aromatic compounds, such as phenanthrene, pyrene or benzo(a)pyrene, alkylphenols, and alkane (40,41). Evidence of the involvement of ProtID 131921 in the degradation of the endocrine disruptor chemical nonylphenol also has been demonstrated (42). Transcriptomic experiments showed that ProtID 139146 and 132579 gene expression is induced after anthracen and anthrone treatments (43).…”
Section: Transcriptomic Analysis (I) Overview Of Gene Expressionmentioning
confidence: 92%
“…Members from CYP5144 and CYP63 exhibit catalytic activities toward environmentally persistent and toxic high-molecular-weight polycyclic aromatic compounds, such as phenanthrene, pyrene or benzo(a)pyrene, alkylphenols, and alkane (40,41). Evidence of the involvement of ProtID 131921 in the degradation of the endocrine disruptor chemical nonylphenol also has been demonstrated (42). Transcriptomic experiments showed that ProtID 139146 and 132579 gene expression is induced after anthracen and anthrone treatments (43).…”
Section: Transcriptomic Analysis (I) Overview Of Gene Expressionmentioning
confidence: 92%
“…Based on this result, it was deduced that the induction of P450 was important for lignin degradation. Overall, the expression patterns observed in T. versicolor grown on a complex lignocellulose substrate suggested that there were diverse strategies for lignin degradation, and thus provided clues about different mechanisms of delignification (Subramanian and Yadav 2009;Syed et al 2010;Ichinose 2013).…”
Section: Validation Of the Gene Expression Profiles By Qrt-pcrmentioning
confidence: 99%
“…The bacterial strain deleted for EcYfcG exhibits an increasing sensitivity toward hydrogen peroxide [19]. In Aspergillus nidulans, the GSTA mutant is sensitive to xenobiotics and heavy metals [20] and in P. chrysosporium, the expression of PcUre2pB1 is upregulated in presence of nonylphenol [21]. In bacteria, EcYfcG might interact with glutathionylspermidin and perhaps utilizes it as a substrate or a regulatory molecule [3,4].…”
Section: Discussionmentioning
confidence: 99%